Primary open angle glaucoma and hypothyroidism - George Kitsos; Chrisavgi Pappa; Agathoklis Tsatsoulis (Clinical Optometry, 2010)
George Kitsos1, Chrisavgi Pappa1, Agathoklis Tsatsoulis21Department of Ophthalmology, Department of Internal Medicine, Medical School, University of Ioannina, Ioannina, Greece; 2Endocrinology Clinic, Department of Internal Medicine, Medical School, University of Ioannina, Ioannina, GreecePurpose: To test the hypothesis: is there an association between primary open angle glaucoma (POAG) and hypothyroidism, and to establish the necessity of routine examination of thyroid function in these patients?Design: Observational cross sectional study.Materials and methods: 78 consecutive patients with a previous diagnosis of POAG and 77 control patients were evaluated for hypothyroidism. The levels of thyroid-stimulating hormone, free thyroxin and triiodothyronine were measured.Results: No patient had hypothyroidism and no correlation was found between glaucoma and either thyroid-stimulating hormone, free thyroxin or triiodothyronine.Conclusion: This study determined there is no an association between glaucoma and hypothyroidism. Therefore, we believe that the systematic screening for hypothyroidism in all patients with POAG is unnecessary.Keywords: primary open angle glaucoma, hypothyroidism, intraocular pressure, thyroid hormones